Bloodbuddy: a Tracking System for Blood Donor Using GPS - Zakaria, Nur Fatini Zahidah; Zainal Abidin, Zulhafiza; Abdullah Zawawi, Muhammad Asyraf; Shuhada, Siti Nur (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2020)
Blood donation is one of the most significant contributions towards the society. Millions of people need blood transfusions each year. Some may need blood during surgery. Others depend on it after an accident or because they have a disease that requires blood components. This study is aim to develop and evaluate the impact of tracking system in the blood shortage situation which is the urgent requirement of the fresh blood and to improve the communication between the hospital and donor. This system will locate the nearest blood donor in cases of emergencies in fastest and easiest way using GPS.The findings on the views of user on the aspects of interface design, navigation and functionality of the web-based application that is developed are presented. Data analysis was done based on the questionnaire received from few users which are student from Universiti Pendidikan Sultan Idris (UPSI). The findings of this study were analysed according to the objectives and the research questions of the project.